The hazard function and its role in a non-parametric duration analysis of enterprises in the Łódzkie Voivodeship - Mikulec, Artur (Funkcja hazardu i jej znaczenie w nieparametrycznej analizie trwania przedsiębiorstw w województwie łódzkim, 2019)
In a duration analysis of enterprises, as a rule there are determined four basic functions related to the time of their duration, i.e.: the density function; the distribution function; the survival function, and the hazard function. It turns out that the hazard function and its cumulative version are the key to understanding modern survival analysis. The aim of the paper is to indicate the best method of the estimation of the values of individual functions in survival analysis based on other functions. The paper provides compiled and classified information on particular functions used in the non-parametric duration analysis of enterprises. It examines some theoretical and practical problems related to the determination of, among others, the hazard function and the cumulative hazard function on the basis of data in cohort tables and the results of the estimation of the survival function with the use of the Kaplan- Meier method. The considerations included in the paper are illustrated with the results of analyses for enterprises established in the Łódzkie Voivodeship in 2001-2015 (including those which went into liquidation)
Econometrics = Ekonometria, 2019, Vol. 23, No. 3, s. 59-75
Keywords: enterprises; duration analysis; hazard function; cumulative hazard function; mean absolute percentage error; przedsiębiorstwa; analiza trwania; funkcja hazardu; skumulowana funkcja hazardu; średni absolutny błąd procentowy